Analisis Kemampuan Awal Dan Kepercayaan Diri Terhadap Kemampuan Komunikasi Matematika - Leny Hartati; Farah Indrawati (Edumatica : Jurnal Pendidikan Matematika, 2019)
This research aims to determine the effect of initial ability and self confidence together on mathematical communication ability, the effect of initial ability on mathematical communication ability, and the effect of self confidence on mathematical communication ability. This study uses a survey method, with multiple regression analysis techniques. Samples were taken using a random sampling technique. The data processing carried out results in a multiple regression equation Y = -2.365 + 0.110 X1 + 0.283 X2, the coefficient of determination (R Square) = 0.22, FCount (0.787) smaller than FTable (3.126), and tCount smaller than tTable . The conclusion of this study is the initial ability and self confidence together do not have a significant effect on mathematical communication ability, the initial ability does not have a significant effect on mathematical communication ability, and self confidence has no significant effect on mathematical communication ability. This study needs to be studied further because only 22% of the value of mathematical communication ability can be explained by using the initial ability value and self confidence, while 78% must be explained by other causative factors. Keywords: Initial Ability, Self Confidence, Mathematical Communication Ability